Visual Inspection with Acetic Acid (VIA) Screening; Six Months Study to Detect Cervical Cancers And Pre-Cancers In Semi Urban Kog East Population Of Women In North Central Nigeria - Onuche, Akogu Simon Peterside; Dare, Omotosho O. (British Journal of Healthcare and Medical Research, 2024)
Cervical cancer is the commonest gyneacological cancer among Nigerian women, contributing to unaccepted morbidity and mortality. Data on cervical cancer in Kogi State is limited. Majority of the cases present late due to low level of awareness and screening uptake. Aims and Objectives: This study aims to determine the prevalence of cervical precancerous lesions using visual inspection with Acetic acid (VIA) among consenting women aged between 22 and 65 years. Materials and Methods: A prospective study conducted from February 2023 to July 2023 in 6 health facilities in Kogi East of Kogi State. 400 consenting women were recruited by a stratified or Random sampling method. The participants completed a semi-structured questionnaire and underwent VIA performed by trained health personnel. Data collected included demographics, life style characteristics and VIA results. This was input and analyzed using SPSS version 20. Results: The study showed a VIA positive rate of 33.8% using the low threshold diagnostic criteria and a 14.3% using the high threshold criteria. This shows a worrisome burden of cervical precancers. 77.5% of the respondents were married. 71% of the respondents had used contraceptives and 53.5% had an early sexually debut (before age 18 years). 11.8% of the respondents had cervicitis. Conclusion: There is urgent need for increased awareness and screening for precancers to promote early detection and reduce cervical cancer incidence. Authorities should demonstrate the W.H.O 90 – 70 – 90 initiative to improve prevention, screening and therapeutic services.